The effects of clinical supervision on supervisees and patient outcomes in psychotherapy – a systematic review and meta-analysis - Schreyer, Bianca; Leithner, Cosima; Eilers, Rebekka; Gossmann, Katharina; Rosner, Rita (Frontiers in Psychiatry, 2025)
ObjectiveSupervisions and case consultations are an essential and often required part of psychotherapeutic training. Despite its importance and ubiquitous use, research is limited, and no quantitative review is yet available. This systematic review and meta-analysis provides an overview of empirical literature on clinical supervision and investigates its effectiveness regarding various outcomes (PROSPERO CRD42024574318).MethodWe conducted a comprehensive literature search up to June 16th, 2025, in the databases Epistemonikos, Cochrane Library, EMBASE, PubMed, PsycINFO and Web of Science. Eligible trials were controlled and uncontrolled trials evaluating the effectiveness of clinical supervision/case consultation with pre- and post-assessment points. Study quality was assessed using Cochrane’s ROBINS-I V2 and RoB-2 tool. Where applicable, outcomes were analyzed using a random-effects model meta-analysis.Results32 studies met the inclusion criteria of which 13 studies could be included in meta-analyses for the outcomes on therapists’ competence, therapeutic alliance and patients’ symptoms. Supervision interventions yielded a small but non-significant effect on symptom reduction in patients favoring the respective supervision interventions. There was a small effect on therapists’ competence and medium effect on therapeutic alliance, which both were non-significant, yet large and significant when compared with passive controls. Regarding the studies included in the review, supervision was mostly reported to have a beneficial effect on therapists’ competence, alliance and patients’ symptoms, while the effects on therapists’ adherence were heterogeneous.ConclusionThese results highlight promising effects of supervision and the need for further investigation of different supervision models. Further research is needed to examine the effectiveness of supervision and investigate potential moderating factors.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024574318.